Defining therapeutic targets by using adenovirus: blocking NF-kappaB inhibits both inflammatory and destructive mechanisms in rheumatoid synovium but spares anti-inflammatory mediators. - Bondeson, J; Foxwell, B; Brennan, F; Feldmann, M (1999)
The role of the transcription factor NF-kappaB in the pathogenesis of rheumatoid arthritis has long been a subject of controversy. We used an adenoviral technique of blocking NF-kappaB through overexpression of the inhibitory subunit IkappaBalpha, which has the advantage that it can be used in the diseased tissue itself, with >90% of the synovial macrophages, fibroblasts, and T cells infected. We found that the spontaneous production of tumor necrosis factor alpha and other pro-inflammatory cytokines is NF-kappaB-dependent in rheumatoid synovial tissue, in contrast to the main anti-inflammatory mediators, like IL-10 and -11, and the IL-1 receptor antagonist. Of even more interest, IkappaBalpha overexpression inhibited the production of matrix metalloproteinases 1 and 3 while not affecting their tissue inhibitor. Blocking NF-kappaB in the rheumatoid joint thus has a very beneficial profile, reducing both the inflammatory response and the tissue destruction. The adenoviral technique described here has widespread applicability, allowing rapid testing of the effects of blocking a potential therapeutic target in either cultures of normal cells or in the diseased tissue itself.